Production of Junar (Citrus sinensis) Wine Using Selected Fermentative Yeast from Indigenous Starter Murcha (Padmakanya Journal of Science and Technology, 2025)
Junar is a citrus fruit of Nepal, which contains a good source of minerals, vitamins and soluble fiber conferring various health benefits. It is mainly found in the mid-hill region of the country. During its peak harvest time, significant amounts are wasted due to fluctuating humidity, insufficient storage facilities, problematic transit, and microbial diseases. The alternative to this is to convert junars into wine. Similarly, for the improvement of flavor, aroma and health benefit parameters of junar wine, screening and isolation of novel yeast strain is beneficial. Therefore, this study aimed to isolate new wine yeast strains from Nepalese indigenous starter named murcha and compare its efficiency for wine preparation. The study was carried out in the food microbiology laboratory of National College, Lainchaur from November 2021 to May 2022. Seven murcha samples (Chamati, Lubu, Panchthar, Pharping, Sankhu, Thali, and Thecho) were used for isolation of potent wine yeasts. Pour plating, sugar fermentation and 18S rRNA gene sequencing were performed for its identification. The junar juice fermentation was carried out for 21 days. The proximate analysis of junar and physio-chemical and sensory parameters of wines were analyzed. From 7 murcha samples, 14 fermentative yeasts and 7 wine yeasts were isolated. Among them, two isolates Saccharomyces cerevisiae Ch1 and Saccharomyces spp Pn4 were screened to be ethanol and acid tolerant strains. The resulting juice yield, moisture content, pH, total soluble solid, titrable acidity and vitamin C content were 56.09%, 90.72%, 4.01, 11.2˚Brix, 0.92% and 34.37%, respectively. Moreover, the ethanol, methanol, total phenolic, total flavonoid content and antioxidant activity were: 8.3% and 7.8%, 0.019% and 0.013%, 484.11 mg GAE/ml and 480.78 mg GAE/ml, 110.12 mg CAE/ml and 125.72 mg CAE/ml and 22.61% and 21.17%, in terms of Ch1 and Pn4 wine accordingly. Based on sensory quality, Ch1 wine was superior to Pn4 wine. Thus, this study concluded that S. cerevisiae isolated from traditional starter murcha was significant for the junar wine production.